2011
DOI: 10.1007/s00280-011-1658-0
|View full text |Cite
|
Sign up to set email alerts
|

Erufosine, an alkylphosphocholine, with differential toxicity to human cancer cells and bone marrow cells

Abstract: Erufosine offers potential as a novel therapeutic for cancer with a reduced toxicity profile to bone marrow cells compared with other agents in this class. Human cancer cells were more sensitive to erufosine than human or mouse bone marrow cells indicating a favorable therapeutic window for erufosine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 39 publications
1
16
0
3
Order By: Relevance
“…Extension of the hydrophobic chain decreased the aqueous solubility of the molecule, which likely self‐assembles into lamellar structures instead of micelles, as was claimed for a closely related structural analogue . As a consequence, the hemolytic potential was significantly reduced, which enabled intravenous (iv) administration that was not feasible with previous APLs …”
Section: Introductionsupporting
confidence: 90%
“…Extension of the hydrophobic chain decreased the aqueous solubility of the molecule, which likely self‐assembles into lamellar structures instead of micelles, as was claimed for a closely related structural analogue . As a consequence, the hemolytic potential was significantly reduced, which enabled intravenous (iv) administration that was not feasible with previous APLs …”
Section: Introductionsupporting
confidence: 90%
“…It remains to be determined whether ErPC3 can elicit an apoptotic effect in these tumor stroma cell populations. However, it has been demonstrated that the toxicity of ErPC3 is selectively greater toward cancer cells than toward human or mouse bone marrow cells (21) and that ErPC3 could stimulate innate immunity by inducing human cord blood cells to form granulocytes/macrophage colonies (39).…”
Section: Discussionmentioning
confidence: 99%
“…Erucylphosphohomocholine (ErPC3; Erufosine [Genzyme]) is a congener of ErPC with higher water solubility and is able to cross the blood-brain barrier (19,20). Similarly to ErPC, ErPC3 exhibits potent antitumor activities in the micromolar range (21) and induces apoptosis in otherwise highly apoptosis-resistant glioblastoma cell lines (15). The mechanism of the cytotoxic and apoptotic actions of ErPC3 in several different cancer cell types has been linked to plasma membrane damage and direct or indirect disruption of Akt signaling (22).…”
mentioning
confidence: 99%
“…The compounds have an insignificant effect on normal lymphocytes, which means they probably do not interfere with the main growth factors, cytokines and chemokines influencing the viability and proliferation of haematopoietic cells. The selectivity against cells derived from blood versus solid tumours was reported for some alkylphosphocholine analogues [35], being the premise of a good therapeutic potential. The behaviour of the prepared compounds is very similar.…”
Section: Antineoplastic Activitymentioning
confidence: 98%